1989
DOI: 10.1246/cl.1989.2205
|View full text |Cite
|
Sign up to set email alerts
|

Laser Breakdown Spectrochemical Analysis of Microparticles in Liquids

Abstract: A focused pulsed laser beam was irradiated on a CaCO3 microparticle in water, and a laser breakdown of single microparticle was induced. In the laser breakdown plasma emission spectrum, the emission lines of Ca I and Ca II were observed, while these lines did not appear for the Ca2+ aqueous solution. Hence this method is effective for analysis of microparticulate impurities in liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…1997; Berman & Wolf 1998), in bulk solutions (Cremers, Radziemski & Loree 1984; Kitamori et al. 1989; Knopp, Scherbaum & Kim 1996; Koch et al. 2004), on droplets (Archontaki & Crouch 1988; Wen-Feng Hsieh 1988; Poulain & Alexander 1995) and in liquid jets (Ito, Ueki & Nakamura 1995; Nakamura et al.…”
Section: Introductionmentioning
confidence: 99%
“…1997; Berman & Wolf 1998), in bulk solutions (Cremers, Radziemski & Loree 1984; Kitamori et al. 1989; Knopp, Scherbaum & Kim 1996; Koch et al. 2004), on droplets (Archontaki & Crouch 1988; Wen-Feng Hsieh 1988; Poulain & Alexander 1995) and in liquid jets (Ito, Ueki & Nakamura 1995; Nakamura et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in ordered to obtain in-situ information of colloids and microparticles in aquatic media, many experimental studies using LIBS have been reported (Kitamori et al 1988(Kitamori et al , 1989a(Kitamori et al , 1989bAjiro et al 1992;Fujimori et al 1992Ito et al 1995Nakamura et al 1996;Hotokezaka et al 2000;Yun et al 2001). The detection of polystyrene ultrafine particles (Kitamori et al 1988(Kitamori et al , 1989aAjiro et al 1992;Fujimori et al 1992), microparticle of CaCO 3 (Kitamori et al 1989), FeOOH (Ito et al 1995;Nakamura et al 1996) and Eu(OH) 3 (Hotokezaka et al 2000;Yun et al 2001) in water using LIBS has been reported for particle counting, elemental analysis and observation of generation of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of polystyrene ultrafine particles (Kitamori et al 1988(Kitamori et al , 1989aAjiro et al 1992;Fujimori et al 1992), microparticle of CaCO 3 (Kitamori et al 1989), FeOOH (Ito et al 1995;Nakamura et al 1996) and Eu(OH) 3 (Hotokezaka et al 2000;Yun et al 2001) in water using LIBS has been reported for particle counting, elemental analysis and observation of generation of precipitation. In our previous studies (Hotokezaka et al 2000;Nagasaki et al 2002aNagasaki et al , 2002b, we showed that LIBS technique was useful for in-situ analysis of particulate europium(III) in aquatic media and CaCO 3 particles in air.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many experimental studies using LIBS have been reported [1][2][3][4][5][6][7][8][9][10][11]. The detection of polystyrene ultrafine particles [1][2][3][4], microparticle of CaCO 3 [5], and FeOOH [6,7] in water using LIBS has been reported for particle counting and elemental analysis. The detection of metal ions, such as Mg, Ca, Na, Ba, Mn, Cu, Fe and Ni, in water using LIBS has also been reported, especially, for the quantitative or multielemental analysis [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%